Aplikasi GIS di dalam pemilihan lokasi "Vertical Park": kajian kes di Kuala Lumpur - Mat Sulaiman, Mohd Khairul Azhar; Maulan, Suhardi; Abu Bakar, Shamsul; Jamil, M.; Uberta, Nangkula; Shariff, R. (Jabatan Seni Bina, Fakulti Kejuruteraan & Alam Bina, Universiti Kebangsaan Malaysia, 2009)
Creating the public spaces for the community has become a crucial need in this nowaday urban township.The advantages in terms of enhacing the social, economical and the environmental issue are undeniable. However, the process of creating this public spaces that required huge amount of area become the main restriction especially in the urban township area. The increasing land value contributed to a new and inovative idea of designing the new concept of having a park which known as a ’Vertical Park’. To bring forward the idea of all the ameneties and facilities that are basically have in the public spaces but in a vertical development to save spaces. However, the most potential site that can comply to all the special requirements needed have to be determined properly, hence the Geographic Information System (GIS) will come in handy to solve the matter. Based on the criterias that have been listed in order to determine the suitable area, several outcomes or potential suggested site has been detected within the area of Kuala Lumpur (Jalan Prima Dua,Metro Prima,Kepong) by using this Geopgraphic Information System.